Majas dan Pembentukannya - Zaimar, Okke Kusuma Sumantri (Makara Human Behavior Studies in Asia, 2002)
Tropes have always attracted the attention of specialists in linguistic as well as in literature, but it seems that there are still some problems which can not be solved, some topics are not yet explained clearly. This research is an effort to understand the formation of tropes from semantic point of view. It does not claim to analyse all tropes, because there are too many tropes to be analysed. By telling about the relation between the signifier, the signified and the referent, this research tries to achieve a better understanding of the problems related to the tropes.